Influences Of Nesting Behaviors In Common Eiders (Somateria Mollissima Sedentaria) In The Western Hudson Bay - Stechmann, Tanner John (UND Scholarly Commons, 2019)
Reproductive decisions of birds are shaped by minimizing predation while meeting physiological needs of parents and offspring. As a result, birds must make decisions about investment in offspring that allows them to maximize their overall fitness. This often drives nesting behaviors and can provide insights into reproductive success. Common eiders (Somateria mollissima) are thought to have high nest attendance (time spent tending the nest) and use substantial energetic resources during breeding. However, the specific behaviors at the nest of these birds are not well studied, with even less known about the Hudson Bay common eider (S. m. sedentaria). The objectives of this study were to determine (1) if colony characteristics and nest age influence nest attendance patterns, (2) if these patterns influence the probability of predation from a specific predator, and (3) what invertebrate resources are available to eiders and what factors impact the availability of those resources. To address our first and second objectives we used data collected during the summers of 2014 to 2017 where we captured nest attendance patterns and their fates at 103 common eider nests using time-lapse imagery from trail cameras. We found eiders spend 95.65% of a day on the nest on average, take 1.4 recesses per day and are gone on recess for an average duration of 43.51 minutes. We did not find nest age or colony characteristics to be major drivers in attendance patterns. Common eider nest predators included arctic foxes (Vulpes lagopus), red foxes (Vulpes vulpes), grizzly bears (Ursus arctos), polar bears (Ursus maritimus), sandhill cranes (Antigone canadensis), herring gulls (Larus argentatus), and bald eagles (Haliaeetus leucocephalus). Annual variation was the most important factor driving nest success. When exploring what predator would consume a nest, we found the best predictor was timing within the breeding season. For our third objective, we collected aquatic invertebrates in June and July of 2016 and 2017 and compared our ...